Prediction of the number of oocytes based on AMH and FSH levels in IVF candidates - Dokuzeylül Güngör, Nur; Gürbüz, Tuğba (Journal of Surgery and Medicine, 2020)
Aim: The purpose of this study was to predict the number of oocytes using anti-Mullerian hormone (AMH) and Follicle Stimulating Hormone (FSH) levels in In Vitro Fertilization (IVF) candidates. Methods: This retrospective cohort study included 121 (23 cases with poor response, 92 cases with normal response, and 6 cases with excessive response) infertile patients. We examined the relationship between AMH and FSH levels and the number of oocytes. The method used in this study was to consider the number of oocytes as the response variable and identify the effective factors. All analyses were performed with free R software. Results: The results show that although the ovarian response is associated with serum AMH levels and the women’s age (P=0.04 and P<0.001, respectively), the negative linear and binomial regression yield a significant collinearity and the natural logarithm of AMH alone can be a good estimate of the ovarian response (P<0.001). ROC curves in logistic regression were used to determine cutoff points. The results of this regression showed that the natural logarithm of AMH with a cutoff value of 1.36 ng/ml can determine the line between the poor and normal ovarian response (P<0.01). The natural logarithm of AMH cannot determine the cutoff value of normal and excessive ovarian response (P>0.05). Conclusion: The use of serum AMH levels is important for the prediction of poor ovarian response.